2013
DOI: 10.3109/08916934.2013.866100
|View full text |Cite
|
Sign up to set email alerts
|

Pemphigus vulgaris autoimmune globulin induces Src-dependent tyrosine-phosphorylation of plakophilin 3 and its detachment from desmoglein 3

Abstract: The cell adhesion molecule plakophilin 3 (Pkp3) plays an essential role in the maintenance of skin integrity and is targeted in certain autoimmune conditions. In one example, we have shown that Pkp3 is instrumental in mediating the discohesive effects of sera from patients with pemphigus vulgaris (PV), a life-threatening autoimmune disease that targets intercellular adhesion in the epidermis. In the present study, we determine the effect of PV autoimmune globulin (PV IgG) on Pkp3 in an in-vitro model of PV. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
0
27
0
Order By: Relevance
“…Mutations in plakophilin 1 and 2 also disrupt desmosome assembly and stability resulting in skin fragility and blistering (McGrath et al 1997; McGrath and Mellerio 2010; Hall 2009). Src inhibition prevented phosphorylation of plakophilin-3, which reduced the disruptive effects of Pemphigus Vulgaris autoimmune antibodies (Cirillo et al 2014). Genetic loss of desmoplakin causes the loss of skin integrity due to intercellular separation and loss of desmosomal linkages to the cytokeratin intermediate filaments (Vasioukhin et al 2001b), and desmoplakin mutations have been found in cases of palmoplantar keratoderma, woolly hair syndrome, and cardiomyopathy (Pigors et al 2015).…”
Section: Epidermis Organization and Regulation Of Homeostasismentioning
confidence: 99%
“…Mutations in plakophilin 1 and 2 also disrupt desmosome assembly and stability resulting in skin fragility and blistering (McGrath et al 1997; McGrath and Mellerio 2010; Hall 2009). Src inhibition prevented phosphorylation of plakophilin-3, which reduced the disruptive effects of Pemphigus Vulgaris autoimmune antibodies (Cirillo et al 2014). Genetic loss of desmoplakin causes the loss of skin integrity due to intercellular separation and loss of desmosomal linkages to the cytokeratin intermediate filaments (Vasioukhin et al 2001b), and desmoplakin mutations have been found in cases of palmoplantar keratoderma, woolly hair syndrome, and cardiomyopathy (Pigors et al 2015).…”
Section: Epidermis Organization and Regulation Of Homeostasismentioning
confidence: 99%
“…A recent study provided evidence that non-desmosomal Dsg3 regulates Src activity, whereby PV IgG reduces the expression of Dsg3 and is associated with a decrease in active Src (Tsang et al 2012). However, another study found that, under some conditions, Src activity promotes PV acantholysis (Cirillo et al 2014). Here, PKP3 is phosphorylated in response to PV IgG leading to dissociation from Dsg3 (Cirillo et al 2014).…”
Section: Desmosomal Cadherinsmentioning
confidence: 99%
“…Extradesmosomal Dsg3 was shown to associate with the cytoskeleton [56] and with E-cadherin, thereby facilitating the activation of Src [57,58], the latter of which is involved in the turnover of AJs [10,38,43] and was implicated in the pathogenesis of PV [12,13,45,64]. Nevertheless, the precise role of E-cadherin in the turnover of desmosomal cadherins and in the disease pemphigus is still not fully understood.…”
Section: Introductionmentioning
confidence: 99%